THE RELATIONSHIP BETWEEN LEADERSHIP BEHAVIOR AND ORGANIZATIONAL CULTURE ON THE ACHIEVEMENT OF THE VISION AND MISSION AT SDN PELANDAKAN 2 - Desyafitri, Euis; Sopidi, Sopidi (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine the relationship between leadership behavior and organizational culture toward achieving the vision and mission at SDN Pelandakan 2, Cirebon City. Using a descriptive qualitative approach, data were collected through direct observation, interviews with the principal and teachers, and document analysis. The results indicate that the principal applied transformational and servant leadership styles, which effectively shaped a positive, collaborative, and family-oriented organizational culture (clan culture). This culture fostered a harmonious work environment, increased teacher motivation, and strengthened commitment to the school’s shared goals. The synergy between leadership and organizational culture significantly contributed to achieving the school’s vision and mission. The study recommends developing a more innovative culture to enhance adaptability to curriculum and technological changes.